A randomized clinical trial of the immunogenicity of 7-valent pneumococcal conjugate vaccine compared to 23-valent polysaccharide vaccine in frail, hospitalized elderly. - C Raina Macintyre (Public Library of Science (PLoS), 2014)
Background Elderly people do not mount strong immune responses to vaccines. We compared 23-valent capsular polysaccharide (23vPPV) alone versus 7-valent conjugate (PCV7) vaccine followed by 23vPPV 6 months later in hospitalized elderly. Methods Participants were randomized to receive 23vPPV or PCV7-23vPPV. Antibodies against serotypes 3, 4, 6A, 6B, 9V, 14, 18C, 19A, 19F, 23F were measured by enzyme-linked immunosorbent (ELISA) and opsonophagocytic (OPA) assays at baseline, 6 months and 12 months. Results Of 312 recruited, between 40% and 72% of subjects had undetectable OPA titres at baseline. After one dose, PCV7 recipients had significantly higher responses to serotypes 9V (both assays) and 23F (OPA only), and 23vPPV recipients had significantly higher responses to serotype 3 (ELISA), 19F and 19A (OPA only). In subjects with undetectable OPA titres at baseline, a proportionately greater rise in OPA titre (P<0.01) was seen for all serotypes after both vaccines. The GMT ratio of OPA was significantly higher at 12 months in the PCV7-23vPPV group for serotypes 6A, 9V, 18C and 23F. OPA titre levels for these serotypes increased moderately after 6 months, whereas immunity waned in the 23vPPV only arm. Conclusion We did not show overwhelming benefit of one vaccine over the other. Low baseline immunity does not preclude a robust immune response, reiterating the importance of vaccinating the frail elderly. A schedule of PCV7-23vPPV prevents waning of antibody, suggesting that both vaccines could be useful in the elderly. Follow up studies are needed to determine persistence of immunity. Trial registration The Australian Clinical Trials Registry ACTRN12607000387426.